Unenlagiid theropods: are they members of the Dromaeosauridae (Theropoda, Maniraptora)? - Agnolin,Federico L. (2011)
In the present paper we analyze the phylogenetic position of the derived Gondwanan theropod clade Unenlagiidae. Although this group has been frequently considered as deeply nested within Deinonychosauria and Dromaeosauridae, most of the features supporting this interpretation are conflictive, at least. Modification of integrative databases, such as that recently published by Hu et al. (2009), produces significant changes in the topological distribution of taxa within Deinonychosauria, depicting unenlagiids outside this clade. Our analysis retrieves, in contrast, a monophyletic Avialae formed by Unenlagiidae plus Aves.